Analysis of spatial transformations and development of the main streets of the historic Nowa Praga district in Warsaw - Krawiec, Iwona (Analiza przekształceń przestrzennych i zabudowy głównych ulic historycznej warszawskiej Nowej Pragi, 2023)
19th and 20th centuries
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2023, nr 3 (75), s. 39-48
Keywords: architektura